Rancangan Perbaikan pada Proses SW-Y9B untuk Mengurangi Pemborosan dengan Pendekatan Lean Manufacturing di PT SIM Bekasi - Basuki . (Politeknik Kelapa Sawit Citra Widya Edukasi, 2013)
This study focused to identifying and eliminating waste through continuous improvement, with the flow of product base on customer demand and in order to make the process more efficient. With a strategy of lean manufacturing, waste indentified with the seven wastes. Base on data collection and processing of data obtained three dominant waste at SW-Y9B process, there are over production (22.2%), transportation (21.75%) and waiting (16.0%). Based on the weight of waste carried out mapping of the seven value stream mapping tools that ultimately produced the three largest mapping tools are Process Activity mapping (score 1,298), Supply chain Response Matrix (score 830) and Demand Amplification Mapping (score 597). After detailed mapping obtained classification of VA = 10%, NVA = 89% and NNVA = 1%. NVA dominated by the activity of storage 86.3% and transportation 7.6%. To reduce the NVA was proposed three improvements: 1) Relocation of production side, which eliminated the transportation distance 4560 meters, saving energy consumption of 409.2 liters per year, saving of forklift operational 9504 hours per year and saving 2 man powers; 2) Making new lay out of production process, to saving area 16 m², reduce WIP 50% and increase productivity by 5.4%; and 3) Change of material delivery lead time from N-2 (two days) to N-1 (one day), can reduce stock of 96%.